Improving identification & management of familial hypercholesterolaemia in primary care: pre- and post-intervention study - Weng, Stephen; Kai, Joe; Tranter, Jennifer; Leonardi-Bee, Jo; Qureshi, Nadeem (Elsevier, 2018)
Background and Aims: Familial hypercholesterolaemia (FH) is a major cause of premature heart disease but remains unrecognised in most patients. This study investigated if a systematic primary care-based approach to identify and manage possible FH improves recommended best clinical practice. Methods: Pre- and post-intervention study in six UK general practices (population 45,033) which invited patients with total cholesterol >7.5 mmol/L to be assessed for possible FH. Compliance with national guideline recommendations to identify and manage possible FH (repeat cholesterol; assess family history of heart disease; identify secondary causes and clinical features; reduce total & LDL-cholesterol; statin prescribing; lifestyle advice) was assessed by calculating the absolute difference in measures of care pre- and six months post-intervention.